(untitled) (Conferencea, 2023)
This study delves into the dynamic landscape of agricultural industrial management, focusing on the strategic implementation of efficiency-driven practices. Examining the transformational potential within the agricultural sector, this research navigates through the adoption of innovative methodologies, technology integration, and structural reforms aimed at optimizing operational efficiency and sustainable growth. Through a lens of proactive change, this study aims to unearth actionable insights that foster the transformation of agricultural industrial management paradigms, steering enterprises towards heightened productivity and competitiveness.